2021
DOI: 10.3390/met11111786
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Characteristics in a Stretch-Based Dimensional Correction Method for Open, Thin-Walled Extrusions

Abstract: Dimensional accuracy of incoming components is crucial for automated welding and assembly in mass volume production. However, thin-walled extrusions made to industrial standards show severe dimensional variations, including gap opening, sidewall inclination, local convexity, and so on. Thus, one major challenge is to provide a low-cost correction method to improve the dimensional accuracy at a level demanded by automated assembly and/or product fit-up. A novel correction method called transverse stretch and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…This technique integrates the stretching and bending mechanisms, mitigating and offsetting the springback. The dimensional deviation is as low as 0.4% of the nominal value in the case of correcting a U channel with an uneven thickness [48]. Hence, this technique can be potentially applied to future high-precision aluminium sheet parts used on EVs.…”
Section: Post-processingmentioning
confidence: 96%
“…This technique integrates the stretching and bending mechanisms, mitigating and offsetting the springback. The dimensional deviation is as low as 0.4% of the nominal value in the case of correcting a U channel with an uneven thickness [48]. Hence, this technique can be potentially applied to future high-precision aluminium sheet parts used on EVs.…”
Section: Post-processingmentioning
confidence: 96%
“…e is the input of the controller, that is, the difference between the measurement result and the given value, also known as the deviation. The controller is discretised and the resulting incremental digital PID control algorithm is given in Equation (2).…”
Section: Single Neuron Pid Algorithm Based On Fuzzy Controlmentioning
confidence: 99%
“…CNC machining is a process method for implementing part machining on CNC machine tools, which uses digital information to control tool displacement and parts, enabling automated machining of variable and complex shaped parts, and has been widely and successfully used in the machinery manufacturing industry. 2 However, in the current CNC machining process, the machining deformation of parts, especially thin-walled parts, is still serious due to the imperfection of the control platform and machining technology. Du et al proposed a multivariate chaotic time series-based prediction method for the motion accuracy of CNC machine tools in order to cope with the information loss caused by unit accuracy time series, so as to achieve the accuracy prediction of motion, and the results showed that the method prediction effect is better and has strong adaptability and practicality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The feasibility of this technique was assessed experimentally with complex U-shape extrusions [15]. The deformation mechanisms of stretching and bending were studied by finite element analysis (FEA) [6]. Also, the die geometry was investigated and optimized, which shows a significant influence on the stress-strain evolutions and the improvement of dimension accuracy.…”
Section: Introductionmentioning
confidence: 99%